A taxonomic revision of the genus Callilepis (Asteraceae) in South Africa - Herman, Paul P.j. (Phytotaxa, 2022)
A complete revision of the genus Callilepis is presented. Most specimens in herbaria were identified either as C. leptophylla or C. laureola because of misconceptions about the other previously described species. A key to all the taxa is provided, full descriptions of all the taxa are drawn up and distribution maps are given. Eleven taxa (ten species, one variety) are recognised. Two new species (C. nepotiana and C. retiefiae) and one new variety (C. laureola var. paucicephala) are described. The name C. glabra is re-instated. Several names are lectotypified. The monotypic genus Zoutpansbergia is included in Callilepis. The genus description is emended to include information of the taxa with corymbose synflorescences and imbricate involucral bracts.